Analysis of mandibular third molar impaction classification with different skeletal malocclusions - Bingül, Muhammet Bahattin; Oğuz, Fırat; Evren, Ayşegül (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Since the third molar teeth are the last to erupt in the oral cavity, they can become more impacted than other teeth. Insufficient retromolar space and the eruption direction of the third molars can affect this situation. The condition, distribution, and prevalence of impacted third molars in skeletal Class I, II, and III anomalies are important in treatment predictability. Purpose: The aim of this study is to classify impacted lower third molars in patients with different skeletal malocclusions. Methods: This retrospective study examined panoramic X-ray records of patients treated at Inonu University Faculty of Dentistry, Department of Orthodontics, between 2014 and 2021. In total, 1219 mandibular third molar teeth were considered. Impacted mandibular third molar teeth of individuals with different skeletal structures were grouped according to the Pell and Gregory, Winter, and Archer classifications. Results: In this study, 37.74% of the participants were male, and 62.26% were female; 40.94% of examined teeth were skeletal Class I, 41.84% were Class II, and 17.23% were Class III. It was determined that 91.63% of all examined teeth were impacted, and 8.37% had erupted. According to the Pell and Gregory classification, 21.41% of teeth were Grade (I), 38.06% were Grade (II), and 40.53% were Grade (III). According to the Winter classification, 3.12% of examined teeth were buccal, 6.89% were horizontal, 23.71% were mesioangular, and 66.28% were vertical. According to the Archer classification, 14.44% of examined teeth were in position A, 30.02% were in position B, and 55.54% were in position C. No statistically significant relationship was established between grades and gender (p>0.05). Conclusion: A relationship was ascertained between the impacted positions of mandibular third molars in different skeletal structures.